2020
DOI: 10.1111/rec.13266
|View full text |Cite
|
Sign up to set email alerts
|

Twenty years of Baltic Boreal coastal meadow restoration: has it been long enough?

Abstract: The restoration of a threatened type of seminatural grassland-the Baltic Boreal coastal meadows-began in Estonia in 1997. The main causes of degradation of these communities were land abandonment and overgrowth by reed. In 2015, we resurveyed 14 sites and classified as (1) permanently managed or (2) restored before 2005, or (3) after 2005. In 2015, all sites were managed under the EU agri-environmental scheme and classified as permanently managed or restored before or after 2005. The resurvey focused on assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 42 publications
0
4
1
Order By: Relevance
“…Our previous study has revealed that in coastal meadows plant species, number does not increase with long-term management [24] and in comparison with other types studied, only a small number of MP species were present here. Therefore, the interpretation of obtained results must be done carefully.…”
Section: Discussioncontrasting
confidence: 52%
See 3 more Smart Citations
“…Our previous study has revealed that in coastal meadows plant species, number does not increase with long-term management [24] and in comparison with other types studied, only a small number of MP species were present here. Therefore, the interpretation of obtained results must be done carefully.…”
Section: Discussioncontrasting
confidence: 52%
“…Most probably, such high variability was caused by very different managemant background and quality of our study sites. In our previous papers, we have demonstrated that both restoration quality and management acitivities have a very strong impact on local plant biodiversity [23,24]. If we deminished our study site selecion in each habitat type by half, almost half of the biodiversity of habitat type could be out of our database, and we recorded almost twice less MP species.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…The Zheng et al [52] study, where OB methods outperformed PB methods, was conducted in a sub-tropical (31 degrees latitude) salt and brackish marsh at the mouth of an estuary along the Yellow Sea, which had plant communities consisting of Phragmites sp., Scirpus triqueter, Carex scabrifolia, and Imperata cylindrica [78] (reeds, bulrushes, and cogon grasses, respectively); these plants are larger, with more showy inflorescences, than the plants of the Aulac marshes. On the other hand, Martinez Prentice et al's [50] study was conducted in a north temperate coastal wetland (58 degrees latitude) along the Baltic Sea, where the plant communities include moor grasses (Molinia caerulea) and rushes (Carex panicea) [79]. These Baltic coastal meadows include vegetation that resembles the grasses of the Aulac marshes in size and inflorescence.…”
Section: Comparison Of Classification Approachesmentioning
confidence: 99%